Ethical requirements for generative AI in brand content creation: a qualitative comparative analysis - Du Plessis, Charmaine (Frontiers in Communication, 2025)
With the rapid integration of Generative AI (GenAI) for brand content creation in content marketing, clearer guidelines for responsible adoption have become important. For this reason, this study identifies and validates ethical requirements for GenAI through qualitative comparative analysis (QCA) of 33 global AI ethical guidelines alongside key ethical concerns in content marketing through the lens of deontology theory. Eight factors became evident, namely, transparency, privacy, intellectual property, fairness, accuracy, accountability, compliance, and discrimination. Intellectual property is demonstrated to be particularly important for protecting brand reputation, which is frequently overlooked in general AI ethical guidelines. While ethical principles for AI use have been well documented, this study focuses on brand content creation, aligning ethical considerations with practical marketing requirements. Consequently, guidelines for GenAI ethics for brand content creation in content marketing are proposed.